Acute pancreatitis associated with scrub typhus. (January 2017) - SV, Padmavathi Devi; M, Aruna; Kumar, Anil CV; Krishna Reddy, Hari; BL, Sangeetha; Siva Kumar, V
Scrub typhus, or tsutsugamushi fever, is a zoonosis of rural Asia and the western Pacific islands. The causative organism, Orientia (formerly Rickettsia) tsutsugamushi, is transmitted to humans by the bite of a larval Leptotrombidium mite (chigger). Scrub typhus may have gastrointestinal presentations, such as acute acalculous cholecystitis, duodenal ulcer perforation, peritonitis and gastric ulceration. Acute pancreatitis with scrub typhus has been reported rarely. We report a patient of scrub typhus complicated by acute pancreatitis and acute kidney injury.